Implementation of “Dzudo from School” Project in Preschool Educational Organizations - o'gli, Shomurodov Sarvar Elbek; Ibodullaevna, Akramova Iqbol (International Journal on Integrated Education, 2023)
The article's goal is to execute a project on judo and to better the way that nursery educational groups classify children for this sport by using surveys. To gain a broad understanding of judo, the piece presents different question formats, offers figures on poll results, examines the scientific and systematic literature, considers the significance and goal of this subject, and draws inferences and offers suggestions.